2001
DOI: 10.1038/35078543
|View full text |Cite
|
Sign up to set email alerts
|

Rme-1 regulates the distribution and function of the endocytic recycling compartment in mammalian cells

Abstract: RME-1 is an Eps15-homology (EH)-domain protein that was identified in a genetic screen for endocytosis genes in Caenorhabditis elegans. When expressed in a CHO cell line, the worm RME-1 protein and a mouse homologue are both associated with the endocytic recycling compartment. Here we show that expression of a dominant-negative construct with a point mutation near the EH domain results in redistribution of the endocytic recycling compartment and slowing down of transferrin receptor recycling. The delivery of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
279
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(302 citation statements)
references
References 38 publications
22
279
1
Order By: Relevance
“…These expression data suggest a functional significance of EHD2 expression in the context of GLUT4 trafficking. Consistent with this possibility, recent studies with EHD1 and its Caenorhabditis elegans homolog RME-1 suggest that these proteins are part of the molecular machinery responsible for recycling of receptors to the plasma membrane (32)(33)(34). Furthermore, connections between EHD1 and endocytosis of IGF-1 receptor in Chinese hamster ovary cells has been described (35).…”
Section: Identification Of Ehd2 In Membrane Fractions From 3t3-l1supporting
confidence: 51%
“…These expression data suggest a functional significance of EHD2 expression in the context of GLUT4 trafficking. Consistent with this possibility, recent studies with EHD1 and its Caenorhabditis elegans homolog RME-1 suggest that these proteins are part of the molecular machinery responsible for recycling of receptors to the plasma membrane (32)(33)(34). Furthermore, connections between EHD1 and endocytosis of IGF-1 receptor in Chinese hamster ovary cells has been described (35).…”
Section: Identification Of Ehd2 In Membrane Fractions From 3t3-l1supporting
confidence: 51%
“…Thus our studies of worm RAB-10 are very likely to be highly applicable to understanding Rab10 function in mammalian systems. The intestinal phenotype caused by loss of rab-10 is very similar to that caused by loss of rme-1, a known endocytic recycling factor Lin et al, 2001). However, unlike rme-1 mutants that also display obvious endocytic defects in oocytes and coelomocytes, we did not detect endocytic defects in oocytes or coelomocytes in rab-10 mutant worms.…”
Section: Rab-10 Is Required For Endocytic Recycling In the Worm Intesmentioning
confidence: 36%
“…Equivalent GFP-fusions for these three proteins have previously been shown to be functional and traffic normally in mammalian cells and/or C. elegans. First we expressed the human transferrin receptor (hTfR-GFP), a marker for clathrin-dependent uptake and rme-1-dependent recycling in mammalian cells (Yamashiro et al, 1984;Burack et al, 2000;Lin et al, 2001). Next we expressed the ␣-chain of the human IL-2 receptor TAC (hTAC-GFP), a marker for clathrin-independent endocytosis and rme-1-dependent recycling in mammalian cells (Caplan et al, 2002;Naslavsky et al, 2004).…”
Section: Gum-1 Mutants Display Rme-1-like Endocytosis Defects In the mentioning
confidence: 99%
“…Golgi transport (20,21). Importantly, we found that loss of RME-1 resulted in dramatically different defects in the subcellular localization of SMA-6 and DAF-4; DAF-4::GFP accumulated in intracellular vesicles, whereas overall levels of SMA-6:: GFP were severely reduced, suggesting that SMA-6 was being inappropriately degraded ( Fig.…”
Section: Clathrin-dependent Endocytosis Is Necessary For Bmp Receptormentioning
confidence: 76%
“…2 A, B, L, and M). Previous work indicated that a block in recycling to the plasma membrane via the ERC often results in intracellular trapping of receptors, whereas blocks in retromer-dependent recycling often results in missorting of receptors to the lysosome, where they are degraded (20,(22)(23)(24). Consistent with this idea, the accumulation of intracellular DAF-4 in the intestine of rme-1 mutants strongly resembled the accumulation of well-characterized ERC cargo hTAC::GFP (human IL-2 receptor α-chain) in rme-1 mutants (Fig.…”
Section: Clathrin-dependent Endocytosis Is Necessary For Bmp Receptormentioning
confidence: 99%